Pengembangan Media Pembelajaran Digital Mata Kuliah Geografi Perkotaan dalam Peningkatan Motivasi Belajar Mahasiswa - Suwarsito Suwarsito; Sutomo Sutomo; Dinny Fauziah (JUITA : Jurnal Informatika, 2011)
The research was motivated by a lack of enthusiasm for learning for students because the delivery of course material which is considered boring by conventional delivery methods without any variation. Based on the reason in this study developed a computer-based digital learning media for Urban Geography course material which is a type of development research. The result of this research is that the media is easy to use learning and increased student motivation to learn which is expressed by 97.67% of the students.